Debris Flow Annual Frequency and Sediment Delivery Variations Compared to Rainfall Changes Over the Last 40 Years (Jiangjia Gully, China) - Zhuang, J.Q.; Cui, P.; Ge, Y.G. (Italian journal of engineering geology and environment, 2011)
Natural hazards occur more frequently due to ongoing global climate change, which has increased the impact of precipitation. Debris flows and their relative activities have also changed over the past 39 years at Jiangjia Gully, a typical debris flow valley with high-frequency debris flows located in the Yunnan Province of China. This paper concentrates on the responses of sediment transportation induced by debris ows at Jiangjia Gully to rainfall change, using statistical analysis of the observation data of debris ows and rainfall. The results showed that: (1) the annual precipitation and rainy season precipitation both decreased in uctuation over the past over 40 years and experienced two high rainfall stages and one low rainfall stage; (2) the days of the daily precipitation that exceeded 20mm, 30mm, and 50mm changed in dissimilarity, and the days with over 20mm of daily precipitation increased slowly and with over 30mm and 50mm both decreased slowly; (3) the sediment amount transported by debris flow generally increased with just a little fluctuation in the past 40 years, which was consistent with the change in annual precipitation and the days with over 20mm of daily precipitation; and (4) the sediment transported by debris ow had a good relativity to annual precipitation and the days with over 20mm of daily precipitation. The frequency of debris flow occurrence has a good relativity to the rainy season precipitation and the days with over 20mm of daily precipitation, and their correlation coefficients are 0.4454 and 0.4737, respectively. The work can provide a scientific basis for the long-term forecast and prevention of debris flows.